2023
DOI: 10.1002/srin.202300446
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Solidification Modeling of Solidification Structure Evolution and Macrosegregation of Round Bloom Continuous Casting Process with Mold Electromagnetic Stirring and Final Electromagnetic Stirring

Yuwei Yang,
Sen Luo,
Weiling Wang
et al.

Abstract: Base on Eulerian‐Eulerian method, a 2D/3D mixed columnar‐equiaxed solidification mathematical model, which takes into consideration the macroscale heat transfer and fluid turbulent flow with microscale grains nucleation and crystal growth, was developed to predict the solidification structure evolution and macrosegregation in continuously cast round bloom. The results show that the M‐EMS could accelerate superheat dissipation and promote grain nucleation in mold, but the horizontal swirl induce by M‐EMS has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Phenomena such as remelting and dissociation occurred near the solidification front, leading to a noticeable refinement of primary dendrites and accelerating the diffusion of solutes enriched in interdendritic spaces. [6] Zhao et al [42] found that the solidification structure of metal was improved with the increase in pulse peak current, but excessive peak currents could induce the Joule heating effect, potentially remelting the grains. [43] Therefore, despite the increase in temperature drop and flow effects with the rise in current, it is essential to prevent excessive Joule heating effects and control energy consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenomena such as remelting and dissociation occurred near the solidification front, leading to a noticeable refinement of primary dendrites and accelerating the diffusion of solutes enriched in interdendritic spaces. [6] Zhao et al [42] found that the solidification structure of metal was improved with the increase in pulse peak current, but excessive peak currents could induce the Joule heating effect, potentially remelting the grains. [43] Therefore, despite the increase in temperature drop and flow effects with the rise in current, it is essential to prevent excessive Joule heating effects and control energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Due to solute redistribution and forced cooling, the heterogeneous defects, such as macrosegregation and shrinkage cavity, are inevitable in continuous casting and are difficult to eliminate through subsequent processes, which seriously affect the quality of steel products. [1,2] Hence, a variety of technologies have been developed to improve the homogeneity of casting blooms, such as electromagnetic swirling flow, [3,4] electromagnetic stirring, [5][6][7] soft or heavy reduction, [8][9][10][11] and so on. The pulsed electromagnetic field, with advantages such as low energy consumption, convenient application, and significant effects, has become a research hotspot in the field of solidification structure refinement technology.…”
Section: Introductionmentioning
confidence: 99%